A socio-demographic profile, growth, nutritional and hygiene status of children of primary and secondary boarding schools of Gandhinagar district: a cross sectional study - Thakor, Nilesh C.; Prajapati, Dipak; Pandor, Jyotsna; Bhagora, Samir (International Journal of Research in Medical Sciences, 2017)
Background: A school is a key location for educating children about health, hygiene and nutrition, and for putting in place interventions to promote the health of children. Objectives: of current study were 1) To study the socio demographic profile of children of boarding schools. 2) To study the growth, nutritional and hygiene status of children of boarding schools. Methods: The study was a cross sectional study. After taking the permission of principal of resident schools and consent of the parents of children, 867 children from 8 boarding schools were interviewed during February-March 2011. A self-administered questionnaire was used for data collection. Results: Age of the study children (total 867) ranged from 5-19 years. (Mean age = 13.80 ± 1.96 years). Out of 867, 434 (49.9%) were boys and 433 (50.1%) were girls. 32.6% belonged to socio economic class IV. There were only 122 (14.1%) children who had been in boarding school since 4 and more than 4 years. Good personal hygiene was observed in only 75 (8.7%) children followed by fair personal hygiene in 292 (33.7%) children and poor personal hygiene in 500 (57.7%) children. 220 (50.8%) female children had fair personal hygiene and 343 (79.0%) male children had poor personal hygiene and this difference was statistically significant. Prevalence of malnutrition in this study was 7.2% (Females = 4.2%; Males = 10.1%; P <0.001).The bulk of the malnutrition cases were constituted by the grade-I P.E.M. cases (66.1%) followed by grade-II P.E.M. cases (25.8%) and there were 5 (8.1%) cases of grade-III malnutrition only in female children. Conclusion:Poor personal hygiene, poor nutritional status among these children needs great attention and health education.